Metakognisi Siswa MTs dalam Menyelesaikan Masalah Sistem Persamaan Linear Dua Variabel (SPLDV) Berdasarkan Gender - Lutfika Zayyenu Zuhairini; Rustanto Rahardi; Santi Irawati (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2023)
The purpose of this study was to describe metacognition in solving problems of the linear equation with two variables based on gender. The research method used is descriptive qualitative. This research was conducted at MTs Plus Darul Ulum in classes VIII-B and VIII-G. Class VIII B is a class with a group of male students, and class VIII G is a class with a group of female students. Then two subjects with high abilities were selected, namely one male student and one female student. The instruments in this study were written test questions and interview guidelines. Metacognition indicators used in this study are knowledge about thinking processes and self-awareness. Based on the results of the study, male and female student subjects with high mathematical abilities in solving SPLDV problems read the problem and underlined the words that were considered important, wrote down the information contained in the problem, and were able to determine the solution plan to be used (elimination, substitution, or graphic) on the component of knowledge about thinking processes. Whereas in the self-awareness component, the two subjects were able to exemplify the variable x for father's age now and variable y for Fitri's age now, write in a mathematical model related to the two-variable linear equation (PLDV), carry out the solution process using method (substitution/ elimination/graph), and substituting the x and y values that have been obtained to find the difference between the father's age and Fitri's age. The results showed that there was no difference. Both subjects involved metacognitive activities on indicators of knowledge regarding thinking processes and self-awareness in solving SPLDV problems.